2015
DOI: 10.1111/edt.12188
|View full text |Cite
|
Sign up to set email alerts
|

Milk activates the expression of cytokines via Nrf2/HO‐1 pathway in human periodontal ligament cells

Abstract: Within the limit of this study, this study demonstrates that exposure of PDL cells to milk is associated with an upregulated expression of several pro-inflammatory proteins and key antioxidant proteins via the activation of Nrf2/ARE pathway in PDL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A further three studies also recommend milk and HBSS along with different natural products . Twenty‐one studies recommended milk in some form in addition to the other media tested, while 13 of these studies exclusively recommended milk . HBSS was found to be the second most recommended individual medium in 16 studies .…”
Section: Resultsmentioning
confidence: 99%
“…A further three studies also recommend milk and HBSS along with different natural products . Twenty‐one studies recommended milk in some form in addition to the other media tested, while 13 of these studies exclusively recommended milk . HBSS was found to be the second most recommended individual medium in 16 studies .…”
Section: Resultsmentioning
confidence: 99%
“…This result was consistent with protein production results. Previous reports showed that pro‐inflammatory cytokines were highly expressed when hPDLCs were kept in milk . Another study found that IL‐1 β expression was upregulated in the co‐culture of mouse periodontal ligament cells and RAW macrophage‐like cells kept in milk for 6 hour.…”
Section: Discussionmentioning
confidence: 95%
“…So far, HBSS and milk are still the tooth‐preserving solutions recommended as a result of their characteristics and ability to maintain the viability of PDLFs . Nevertheless, each has some disadvantages: HBSS is not easily accessible at the scene of accidents; and milk has been shown to have some negative effects on cells and on the formation of PDL tissue .…”
Section: Discussionmentioning
confidence: 99%